Research and practice of OTN controller northbound unified interface model - Yanxia TAN; Yanlei ZHENG; Guangquan WANG; He ZHANG (Dianxin kexue)
In the software defined optical transport network (SDOTN) architecture, the manufacturer’s controller system is required to be connected to the optical transport network (OTN) orchestrator system through the northbound interface.However, there is currently no unified northbound interface standard, which brings many problems to the automatic provisioning of cross-domain and cross-vendor end-to-end services in SDOTN.The status and problems of OTN controller northbound open interface standards were expounded, and the current mainstream transport application programming interface (TAPI) and abstraction and control of traffic engineering network (ACTN) northbound interface standards from the perspective of network models were compared and analyzed.Finally, the research practice of China Unicom in the standardization of ACTN unified interface model and the construction of management and control system were introduced, and an outlook on the follow-up research and development direction was provided.